3D Analysis of Graveyard Trees in the Wake of COVID-19: 3D Analysis of Graveyard Trees in the Wake of COVID-19 - Pervaiz, Shazia; Khan, Filza Zafar; Javid, Kanwal (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Covid-19 presented the new perspective of urban green space to battle the pandemic crisis globally. The havoc of Coronavirus became more deadly with the combination of foul air which is one of the urban challenges birthed by the shrinkage of green cover. Significantly, urban trees are valuable and cost-effective solutions to gobble up the concentration of air-borne particulates from the environment. Thus, by keeping in view the importance of trees in the era of COVID-19, the 3D (density, diversity and durability) analysis has been carried out for the first time in the smog prone city (Lahore) with the objective to examine the potential of green cover in the urban graveyards. The current research consists of two data sources. The first source is a Muslim Graveyard and the second one is a NonMuslim (Christian) Graveyard. Field assessment was carried out in graveyards using a global positioning system. The observation data of trees assessment was used in terms of tree cover, diversity and their physical condition. Results of the study showed that both of the graveyards are deficient in tree cover. Thus, it was concluded from the findings that the unsatisfactory state of tree health and diversity could neither maintain the surrounding environment by absorbing carbon dioxide nor defeat the particulate pollutants. Moreover, the present study will prove to be a valuable source of information for government departments such as forest and urban planning to realign strategies to provide healthy air to breathe, mitigate the risk of pandemic and minimize environmental pollution i.e., smog.